CALCULATION OF THE THREE-LAYER PLATE BY THE METHOD OF FINAL ELEMENTS TAKING INTO ACCOUNT CREEP OF THE CENTRE - B. M. Yazyev; A. S. Chepurnenko; S. V. Litvinov; S. B. Yazyev (Вестник Дагестанского государственного технического университета: Технические науки)
The resolving equations of finite element method for the problem of bending of three-layer flexible plate taking into account creep were obtained. These equations are valid for arbitrary laws of connection between creep strain and stress. In deriving the basic relations of FEM we took into account only the work of aggregate on shift. Comparison of the solutions in the FEM with the resultsobtained by finite difference method with the work of bearing layers was made.